Revitalisasi tas Koja Baduy melalui pendekatan Indigenous Design Thinking dan ATUMICS dalam integrasi tradisi dan desain kontemporer - Junaidi Salam; Nina Maftukha (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
This study aims to revitalize the Baduy Koja Bag through an Indigenous Design Thinking approach and the ATUMICS method as an effort to integrate traditional values with contemporary design needs. The Koja Bag, as a distinctive craft of the Baduy community, serves not only a practical function but also embodies strong philosophical, ecological, and spiritual values. Indigenous Design Thinking is employed to explore the meanings, symbolism, and social practices embedded in the Koja Bag, while the ATUMICS method provides an analytical framework for design elements, including technique, material, utility, icon, concept, and shape. The results indicate that the design revitalization process successfully preserved approximately 70 percent of the Koja Bag’s traditional elements, particularly in weaving techniques, the use of local materials, and visual symbolism. Meanwhile, around 30 percent of the design elements were selectively revitalized to enhance product ergonomics and functionality without diminishing cultural identity. The integrated contemporary elements include a transformation of the silhouette into a hobo bag form, the addition of a buckle system on the strap, and the use of inner lining to improve everyday comfort. These quantitative findings confirm that culture-based design innovation can be achieved through measurable and sustainable contextual transformation. The revitalization of the Koja Bag contributes to the preservation of traditional crafts amid globalization while opening opportunities for sustainable creative economic development for the Baduy artisan community.